Impact of a model of care for heart failure in‐patients to reduce variation in care: a quality improvement project. Issue 4 (22nd April 2021) - Hopper, Ingrid; Easton, Kellie; Bader, Illona; Campbell, James; Busija, Lucy; Markey, Peter; Bergin, Peter; Kaye, David
Abstract: Background: We identified variation in delivery of guideline recommended care at our institution, and undertook a project to design a heart failure (HF) model of care. Aim: To maximise time patients with HF spend well in the community by delivering best practice guidelines to reduce variation in care improving overall outcomes. Methods: This quality improvement project focused on reducing variation in process measures of care. The HF model of care included electronic HF care bundles, a patient education pack with staff training on delivering HF patient education, referral of all HF patients to the Hospital Admissions Risk Program for phone call within 72 h, and a nurse–pharmacist early follow‐up clinic. Outcomes were assessed using interrupted time series analyses. Results: The pre‐intervention group comprised 1585 patients, and post‐intervention 1720 patients with a primary diagnosis of HF admitted under general cardiology and general medicine. Interrupted time series analysis indicated 30‐day readmissions did not change in overall trend (−0.2% per month, P = 0.479) but a significant immediate step‐down of 7.8% was seen ( P = 0.018). For 90‐day readmissions, a significant trend reduction over the time period was seen (−0.6% per month, P = 0.017) with a significant immediate step‐down (−9.4%, P = 0.001). Emergency department representations, in‐patient mortality and length of stay did not change significantly. Improvements in process measures were seen at audit. Conclusion: This model of care resulted in overall trends of reductions in 30‐ and 90‐day readmissions, without increasing emergency department representations, mortality and length of stay. This model will be adapted as the electronic medical record is introduced at our institution.